The Role of Legislation to protect Children in Cyberspace - Abdelmalik, SAOULI (Journal of Social Sciences and Humanities, 2024)
In this article I discussed the legal framework in wich the child practices his cyber media activity in a safe condition, and under the protection of the law, because this space is open to all possibilities, it has many positives, but its negative may come upon the lives of this group and destroy it, away of the supervision of parents and relatives, this child does not know the harm of this practice, which may lead him to addiction, or harm his sanity and behavior, when he exposed to contents whose harm may be obvious or hidden, on the other hand may com across content creators, andividuales or gangs he cannot escape his attack, so the legislator took into account these practices with legeslation protecting this category, any transgression against them is considered a misdemeanor punishable by law.